2009
DOI: 10.1021/ma900747q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Poly(ester−ether)s: Copolymers from 1,4-Dioxan-2-one and d,l-3-Methyl-1,4-dioxan-2-one

Abstract: Synthesis of random copolymers by the nonsequential polymerization of 1,4-dioxan-2-one with D,L-3-methyl-1,4-dioxan-2-one was first investigated using a range of classical initiators. Experimental conditions such as temperature and initiator concentrations were varied to achieve reasonable monomer conversions and molar masses. In general, copolymers were slightly enriched in 1,4-dioxan-2-one. On the basis of block lengths of the respective (co)monomer sequences, it is proposed that the copolymer consists of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The degradation rate of poly(ester-ether)s could also be controlled by copolymerizing dioxanone with methyl dioxanone (MeDX). [127][128][129] Indeed, the introduction of MeDX units in a PDX backbone alters the crystallinity of the resulting copolymer, enhancing hydrolytic cleavage and degradation. In vivo degradation studies conducted on PLCL tubular scaffolds showed a slow degradation (mass loss of 81% noted for an implanted period of 15 weeks), whereby the caprolactone units degraded faster than the lactide units.…”
Section: Biodegradabilitymentioning
confidence: 99%
“…The degradation rate of poly(ester-ether)s could also be controlled by copolymerizing dioxanone with methyl dioxanone (MeDX). [127][128][129] Indeed, the introduction of MeDX units in a PDX backbone alters the crystallinity of the resulting copolymer, enhancing hydrolytic cleavage and degradation. In vivo degradation studies conducted on PLCL tubular scaffolds showed a slow degradation (mass loss of 81% noted for an implanted period of 15 weeks), whereby the caprolactone units degraded faster than the lactide units.…”
Section: Biodegradabilitymentioning
confidence: 99%
“…Inspired by the PLGA family, our group reported on the synthesis and homopolymerisation of a dioxanone analogue, namely MeDX (Lochee et al 2009(Lochee et al , 2010 and its copolymerisation with dioxanone to produce a range of random copolymers (Wolfe et al 2011). Figure 2 gives the structures of 1,4-dioxan-2-one and 3-methyl-1,4-dioxan-2-one.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(dioxanone-co-methyl dioxanone) [P(DX-coMeDX)] random copolymers were synthesised by procedures previously reported by Lochee et al (2009). Diblock polycaprolactone-b-poly(dioxanone-co-methyl dioxanone) [PCL-b-P(DX-co-MeDX)] polymers were synthesised as described previously (Goonoo et al 2012).…”
Section: Synthesis Of Copolymersmentioning
confidence: 99%
“…The degradation rate of poly(ester‐ether)s could also be controlled by copolymerizing dioxanone with methyl dioxanone (MeDX). Indeed, the introduction of MeDX units in a PDO backbone alters the crystallinity of the resulting copolymer, enhancing hydrolytic cleavage and degradation. In vivo degradation studies conducted on PLCL tubular scaffolds displayed a slow degradation speed (mass loss of 81% noted for an implanted period of 15 weeks), whereby the caprolactone units degraded faster than the lactide part .…”
Section: Controlling Biodegradationmentioning
confidence: 99%